Effectiveness of cognitive rehabilitation on mild cognitive impairment using teleneuropsychology (2023)
The COVID-19 pandemic has affected the continuity of cognitive rehabilitation worldwide. However, the use of teleneuropsychology to provide cognitive rehabilitation has contributed significantly to the continuity of the treatment. Objectives: To measure the effects of cognitive telerehabilitation on cognition, neuropsychiatric symptoms, and memory strategies in a cohort of patients with mild cognitive impairment. Methods: A sample of 60 patients with mild cognitive impairment according to Petersen’s criteria was randomly divided into two groups: 30 treatment cases and 30 controls (waiting list group). Subjects were matched by age, sex, and Montreal Cognitive Assessment. The treatment group received ten cognitive telerehabilitation sessions of 45 minutes duration once a week. Pre-treatment (week 0) and post-treatment (week 10) measures were assessed for both groups. Different linear mixed models were estimated to test treatment effect (cognitive telerehabilitation vs. controls) on each outcome of interest over time (pre/post-intervention). Results: A significant group (control/treatment) x time (pre/post) interaction revealed that the treatment group at week 10 had better scores in cognitive variables: memory (RAVLT learning trials p=0.030; RAVLT delayed recall p=0.029), phonological fluency (p=0.001), activities of daily living (FAQ p=0.001), satisfaction with memory performance (MMQ satisfaction p=0.004) and use of memory strategies (MMQ strategy p=0.000), as well as, and a significant reduction of affective symptomatology: depression (GDS p=0.000), neuropsychiatric symptoms (NPI-Q p=0.045), forgetfulness (EDO-10 p=0.000), and stress (DAS stress p=0.000). Conclusions: Our study suggests that CTR is an effective intervention.